Study on the Behavioral Health Risk Factors of Sewing Industry Workers in Bulgaria (European Journal of Marketing and Economics, 2025)
The chronic non-communicable diseases in the last twenty years have been a major priority of the World Health Organisation (WHO) due to their epidemic character. These diseases lead to morbidity, mortality and invalidization which have a great health, social and economic effect. The main reason for triggering the chronic non-communicable diseases are the behavioral health risk factors of life such as nutrition, physical activity, smoking and the use of alcohol. The risk factors are characteristics at the biological, psychological, family, community, or cultural level that precede and are associated with a higher likelihood of negative outcomes. Since these factors are manageable, it is essential to carry out targeted health policy among the working people aiming at their optimization which correlates to the improved health status of the population as a whole. A suitable group for study of the behavioral risk factors are the organized groups of workers within enterprises.Our study is conducted among 503 working people in an enterprise of the sewing industry in Bulgaria in 2015.
Keywords: behavioral health risk factors, health status, nutrition, locomotor activity, concentated alcoholoc drinks